Manifestaciones alérgicas en oftalmología. 1. Retinitis alérgica a infección focal estafilocóccica: su importancia diagnóstica y tratamiento exclusivo con autoalérgenos - Vieto A., Pedro L. (1960)
Two clinical cases diagnosed as allergic retinitis due to Staphylococcus are reported for the first time. The literature is revised as to whether the retina has been shown to be a shock organ and whether Staphylococcus can act as a common allergen. The method used in the diagnosis is described and involves the following data : family or personal allergy antecedents, sensitivity to staphylococcus intradermal test (immediate positive reaction), isolation of pathogenic strains even from apparently healthy nasal mucose. The authors, with the diagnosis established, proeeded to an exclusive treatment with auto-allergens, obtaining in both cases and in a short time, the res/i/utio ad integrum of the majority of the retinian lesions. Retinian allergy, to allergens from strains of Staphylococcus aureus and Staphylococcus albus is thus demonstrated.